Diagnosis of Pulmonary Tuberculosis in Children: Assessment of the 2012 National Institutes of Health Expert Consensus Criteria - Zar, Heather J. (Clin Infect Dis, 2015)
Background. The 2012 National Institutes of Health (NIH) consensus criteria for standardized diagnostic categories of pulmonary tuberculosis in children have not been validated. We aimed to assess the NIH diagnostic criteria in children with culture-confirmed pulmonary tuberculosis and those in whom tuberculosis has been excluded. Methods. We performed a retrospective analysis of consecutive children hospitalized with suspected pulmonary tuberculosis in Cape Town, South Africa, who were enrolled in a diagnostic study. Children were categorized as definite tuberculosis (culture positive), probable tuberculosis (chest radiograph consistent), possible tuberculosis (chest radiograph inconsistent), or not tuberculosis (improved without tuberculosis treatment). We applied the NIH diagnostic categories to the cohort and evaluated their performance specifically in children with definite tuberculosis and not tuberculosis. Results. Four hundred sixty-four children (median age, 25.1 months [interquartile range, 13.5–61.5 months]) were included; 96 (20.7%) were HIV infected. Of these, 165 (35.6%) were definite tuberculosis, and 299 (64.4%) were not tuberculosis. If strict NIH symptom criteria were applied, 100 (21.6%) were unclassifiable including 21 (21.0%) with definite pulmonary tuberculosis, as they did not meet the NIH criteria due to short duration of symptoms; 71 (71%) had cough <14 days, 48 (48%) had recent weight loss, and 39 (39%) had fever <7 days. Of 364 classifiable children, there was moderate agreement (κ = 0.48) with 100% agreement for definite tuberculosis and moderate agreement for not tuberculosis (220 [60.4%] vs 89 [24.5%]). Conclusions. Entry criteria for diagnostic studies should not be restrictive. Data from this analysis have informed revision of the NIH definitions.